1991
DOI: 10.1111/j.1600-0447.1991.tb03187.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the Canary Islands, 1977–1983

Abstract: We studied suicide in the Canary Islands between 1977 and 1983 and found 775 cases, twice the official number of 381. This indicates the lack of validity and reliability of official figures for suicide in Spain today. The figures reveal an upward trend in the Canary Islands, with the annual rate of 6.81 per 100,000 in 1977 having increased to 10.64 per 100,000 in 1983. There were no significant differences in the frequency of suicide according to season, month or day of the week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…One of these studies concluded fairly reliable suicide statistics, one 0-10% under-reporting and one concluded 11-30% under-reporting. Twenty-one studies got a sum score 10-14 [8,9,11-13,15-17,20-23,27-32,35,37,38] and seven studies sum score ≤9 [10,14,18,19,25,26,34]. Five of the studies with quality sum score ≤9 concluded > 30% under-reporting or poor suicide statistics, one concluded 0-10% under-reporting.…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies concluded fairly reliable suicide statistics, one 0-10% under-reporting and one concluded 11-30% under-reporting. Twenty-one studies got a sum score 10-14 [8,9,11-13,15-17,20-23,27-32,35,37,38] and seven studies sum score ≤9 [10,14,18,19,25,26,34]. Five of the studies with quality sum score ≤9 concluded > 30% under-reporting or poor suicide statistics, one concluded 0-10% under-reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, all such deaths were assumed to be bona fide suicides (32). However, some suicides may not be coded as such on death certificates (9,25,26); so we also identified other suspicious deaths through the medical index (32). For each candidate case, the patient's complete (inpatient and outpatient) medical records were reviewed until it was possible to know the death was not a suicide.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have found no association between suicide and birth date (17)(18)(19)(20)(21)(22) but found fewer suicides during the quarter of the year preceding the birth date (4%) and a significant excess (43 2) during the quarter after (23,24). However, studies that address suicide timing from death certificate data may be biased by errors in the reported date of suicide and by the fact that suicides are sometimes certified as deaths due to other causes (9,(25)(26)(27). Rich et al (28) deemed the interval between the suicidal act and subsequent death to be significant, although others have found the interval to be inconsequential for research purposes (14,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Canary Islands the suicide rate during the period 1977-1983 was 8.1 per 100,000 5 , increasing the risk of suicide with age and showing is the highest values for separated and divorced 6 people, but parasuicide rates are unknown.…”
Section: Introductionmentioning
confidence: 99%